Pengembangan Modul Pelatihan Matan Al-Jurumiyah Berbasis PBL Di Kelas X Aliyah Muallimin Univa Medan - harahap, Khairunnisa; Nasution, Sahkholid; Walad Ahkas, Akmal (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
This study aims to develop a problem-based learning (PBL)-based Matan Al-Jurumiyah training module for Class X Aliyah at Muallimin Univa Medan. The research method used is research and development (R&D) by applying the ADDIE model, including analysis, design, development, implementation, and evaluation. The module development process involved analyzing learner needs, product design, validation testing by material experts and media experts, as well as limited and extensive trials with the participation of 30 students at Madrasah Aliyah Muallimin Univa Medan. The module feasibility test showed an average score of 92.5%, indicating an excellent level of feasibility. The practicality test, involving 5 students in the limited test and 30 students in the broad trial, resulted in an average score of 87.28%, indicating a high level of practicality. The module effectiveness test, with a normalized gain (N-Gain) score of 0.58%, showed the effectiveness of the module in improving students' understanding of Matan Al-Jurumiyah. This research makes a positive contribution to creating a practical and effective training module to improve students' understanding of Matan Al-Jurumiyah in Class X of Aliyah Muallimin Univa Medan